Segmented constitutive relationship of weakly cemented sandstone and numerical implementation based on homogeneity - Wang Hong; Zuo Yu-jun; Zhang Lei (Scientific Reports)
Abstract A deep understanding of the mechanical properties of weakly cemented sandstones in coal-bearing strata is crucial for ensuring the safety of coal mining operations. This study addresses this problem by investigating the deformation characteristics of such rocks through triaxial compression tests, and a novel piecewise constitutive model was developed, integrating the Double-strain Hoek model (TPHM) and statistical damage theory. The outcomes highlight several key findings: (1) The experiments revealed a distinct compaction stage in weakly cemented sandstone, which becomes shorter with an increase in confining pressure, highlighting a significant mechanical property of these rocks. (2) The piecewise constitutive model demonstrates effectiveness in capturing the compaction stage, the elastic deformation stage, and the post-damage deformation phase, with excellent agreement between the model predictions and experimental data. (3) By incorporating the model into FLAC3D and considering rock homogeneity, the study demonstrates the capability to calculate and predict the stress field migration and the evolution of damaged zones during the failure process of weakly cemented sandstone under various confining pressures. These findings not only contribute to a deeper understanding of the mechanical behavior of weakly cemented sandstones but also provide a theoretical framework for evaluating the stability of mines (especially roof and floor slabs) during coal mining activities in such rocks.